Analisis Pelaksanaan Sistem Rujukan Berjenjang Bagi Peserta JKN di Puskesmas X Kota Surabaya - Dwi Ratnasari (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2017)
The era of National Health Security (NHS) enacted tiered referral system start in primary health care. High number of referrals at Public Health Center (PHC) X indicates that the implementation of referral system did not go well. The objectives of this study is to confirm implementation of refferal system in PHC in the era NHS based on the regulations and policies. This was descriptive observational research and cross sectional design with implementation research method. This research used triangulation to get deep information toward referral documents include referral data, registration book, medical records, referral letter, interview with refferal officer, and observation without intervention. This research was conducted at PHC X Surabaya on the Februari-March 2017. The results showed implementation of refferal system has appropriate with the regulations and the guidelines. The implementation has appropriate with 7 section on The Regulation of Health Minister No.1 of 2012. The implementation has appropriate with Guidelines of National Health Refferal include requirement to refer patient, refferal clinical procedure, and refferal administrative procedure, however there is not appropriate implementation: informed consent, contact to refferal destination healthcare, and print out of refferal paper. Recommendation for PHC is to do informed consent and print refferal letters 2 copies.Keywords: national health security, public health center, refferal system